Métodos geofísicos aplicados a prospecção mineral na região do Igarapé Chega Tudo, Maranhão - Brasil - ORTEGA GONZALEZ, Moisés (Universidade Federal do Pará, 2014)
This work of geophysical prospecting was carried out on a NW-SE geological lineament zone from Chatão - on the right side of Gurupi river up to 5 km beyond Chega Tudo in the State of Maranhão. The field work with the application of magnetic (total field), radiometric, electroresistivity (Schlumberger, Wenner and Half-Schlumbergere) and EM (Sligram) methods was carried out in two stages: a) reconnaissance survey of a 22 km2 area with magnetic and radiometric methods, and b) detailed survey of a 3.5 km2 area with electroresistivity and EM methods. The objectives were to study the main geoelectrical structures associated with mineralized zones, and to select among the used geophysical techniques the one with greater resolution to locate sub-surface quartz veins with gold mineralization. The magnetic method shows a large anomaly in the NE region of the area of reconnaissance, whereas the radiometric method indicates only the background value everywhere. Therefore the latter will be not discussed. The electroresistivity and EM surveys indicate many important anomalies on the detailed area. The electroresistivity and magnetic interpretation were carried out by computacional techniques whereas the EM data were interpreted by phase diagrams. The results show a good correlation between the magnetic and electroresistivity anomalies and the mineralized zone. The EM method was not found effective because it could not discriminate the anomalies inside and outside the mineralized zone. All anomalies were tested with well logs. Since the studied area has the same degree of difficulties for geological prospecting as any other similar area in the Amazon region, the results presented here show that the magnetic and electroresistivity methods, which turned out to be very effective as exploration tools for prospecting gold at Chega Tudo region, could be applied to any other environment with similar geological characteristics.